Writing in Place with Jamaica Kincaid’s A Small Place - Jesse Curran (Radical Teacher, 2025)
This "Teaching Note" explores the transformative power of Jamaica Kincaid's A Small Place in encouraging students to use literary theory to analyze the complex historical dimensions of their places. The note begins with my personal recognition of the book's role in my own intellectual development and realization of complicity in neocolonial subjugation. Building on its enduring power and the vulnerability the text creates for the reader, students can experiment with adopting Kincaid's rhetorical position and strategies in order to write creative travelogues of their places. The essay also considers the value of offering creative assignments in order to address student fatigue and centralize lived experience as highly relevant to thinking theoretically.